Beban ekonomi yang ditanggung pasien dan keluarga akibat penyakit stroke: studi literatur - Honesty Fadhilah; Vetty Yulianty Permanasari (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Economic burden borne by patients and families due to stroke: literatur reviewPurpose: Stroke to this day is still a disease that carries a high disability, so that in the future it requires very expensive costs, and has an impact on the socio-economic consequences for patients and their families. Therefore, this study aims to estimate the causes of costs that cause economic burden due to stroke. Methods: The method used is content analysis by searching literature review from various sources, both in the form of journals and textbooks from national and international levels.Results: The literature study shows that direct medical costs in the form of rehabilitation costs and nursing care were identified as the main contributors that caused a high economic burden due to stroke.Conclusions: The high cost incurred causes families to experience catastrophic financial disasters, resulting in a decrease in the level of welfare. Social preventive measures are needed to reduce the magnitude of the prevalence of stroke to be able to reduce this cost burden in order to protect every household from the financial threat of a stroke.